Wisdom as foundation for a fraternal and ethical existence in the Pauline Theology - Rodríguez Delgado, Emerson (2014)
Paul shifts his presentation of the revelation of divine wisdom, from a paradoxical tone in 1Cor 1,6-16 to a more confrontational and revelatory tone in 1 Cor 2,6-16, in order to provide the necessary elements to the believers to discern the dynamic relationship with “νοῦς Χριστοῦ” through the Spirit. From his reception in the Baptism, the believer is granted a new ontological identity by this pneumatic presence. In this fashion, the believers, “who love God – the mature/perfect,” communicate God’s salvific reality in his cruciform manifestation of Divine wisdom in Christ. Therefore, a “mature/perfect” believer lives according to his new identity when takes in the “logos of the cross” by an attentive listening and rendering into a pneumatic life that discerns and acknowledges Christ-event’ staurological and kenotic reality amidst the community, which is materialized in an ethical and fraternal existence with other